Overexpression of growth hormone improved hepatic glucose catabolism and relieved liver lipid deposition in common carp (Cyprinus carpio L.) fed a high-starch diet - Wu, Yunya; Li, Rui; Wu, Xingxing; Guo, Wei; Zhong, Wenrong; Li, Yongming; Song, Yanlong; Tao, Binbin; Chen, Ji; Han, Dong; Xie, Shouqi; Wang, Yaping; et al. (Frontiers in Endocrinology, 2022)
Growth hormone (GH) is important for regulating insulin secretion and carbohydrate metabolism, and its role in mammalian models of diabetes is relatively worked out. Although some fish species were used as models for diabetes research, the effects of GH on insulin and glucose catabolism and anabolism in these models remain to be clarified. In this study, we investigated the effect of GH on insulin and glucose catabolism and anabolism in an omnivorous fish using GH transgenic (T) common carp that consistently overexpressed GH and wild-type (WT) common carp. We compared the intestinal morphology, and digestive and absorptive capacity of fish fed commercial feed. We also analyzed the growth performance, insulin level, glucose catabolism and anabolism, lipid deposition, and lipid catabolism and anabolism in T carp and WT carp fed diets containing either 30% or 40% starch. In the intestine of T carp, α-amylase activity was enhanced, the number of goblet cells and intestinal villi surface area was increased, and the expression level of glucose transport protein-related genes (glut2 and sglt1) was upregulated when compared to these indicators in WT carp. When fed either a normal or high-starch diet, the growth performance of T carp was better than that of WT carp. Compared with WT carp, serum insulin was increased and glucose was decreased, hepatic expression level of igf-1 and glycolysis-related genes was increased, and the activity level of a hepatic enzyme related to glycolysis was enhanced in T carp. When fed with a high-starch diet, the serum alanine aminotransferase activity, hepatic lipid content, and malondialdehyde content were significantly lower in T carp than in WT carp. These results indicated that overexpression of GH (1) enhanced carbohydrate digestion and absorption in the carp intestine, (2) did not induce insulin resistance and improved glucose catabolism and utilization in carp, and (3) relieved liver lipid deposition. Our data might provide new insights into potential ways to improve glucose utilization in fish and diabetes treatments.